Clinical value of serum complement component 1q levels in the prognostic analysis of aneurysmal subarachnoid hemorrhage: a prospective cohort study - Wang, Linjie; Zhou, Haotian; Zheng, Wenhao; Wang, Heng; Wang, Zheng; Dong, Xiaoqiao; Du, Quan (Frontiers in Neurology, 2024)
Objective To analyze the relationship between serum complement component 1q (C1q) levels and functional prognosis in patients with aneurysmal subarachnoid hemorrhage (aSAH), and to reveal its clinical value.In this prospective cohort study, we collected clinical data of aSAH patients admitted to the Department of Neurosurgery, Hangzhou First People's Hospital from January 2020 to October 2022. Parameters such as serum C1q levels, Hunt-Hess grade, modified Fisher grade, and the modified Rankin scale (mRS) at three months were included for evaluation. Patients were grouped based on the occurrence of delayed cerebral ischemia (DCI). Spearman rank correlation test and Kruskal-Wallis rank sum test were used to analyze the correlation between serum C1q levels, disease severity, and prognosis. Potential risk factors affecting prognosis and the occurrence of DCI were screened through Independent sample t-test or Mann-Whitney U test. Variables with significant differences (P<0.05) were incorporated into a logistic regression model to identify independent risk factors affecting prognosis and DCI occurrence. Serum C1q levels were plotted as a ROC curve for predicting prognosis and DCI, and the area under the curve was calculated.Results A total of 107 aSAH patients were analyzed. Serum C1q levels positively correlated with Hunt-Hess grade, modified Fisher grade and mRS (all P<0.001). Significant differences were observed in C1q levels among different Hunt-Hess grade, mFisher grade and mRS (all P<0.001). Notably, higher serum C1q levels were seen in the poor prognosis group and DCI group, and correlated with worse prognosis (OR=36.927, P=0.015), and an increased risk for DCI (OR=17.334, P=0.039). ROC analysis revealed the significant discriminative power of serum C1q levels for poor prognosis (AUC 0.781; 95%CI 0.673-0.888; P<0.001) and DCI occurrence (AUC 0.763; 95%CI 0.637-0.888; P<0.001). Higher C1q levels independently predicted a poor prognosis and DCI with equivalent predictive abilities to Hunt-Hess grade and modified Fisher grade (both P<0.05).High levels of C1q in the blood is an independent risk factor for poor prognosis and the development of DCI in patients with aSAH. This can more objectively and accurately predict functional outcomes and the incidence of DCI. C1q may have a significant role in the mechanism behind DCI after aSAH.